2005
DOI: 10.1111/j.1460-9568.2005.04451.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal minocycline attenuates peripheral inflammation‐induced hyperalgesia by inhibiting p38 MAPK in spinal microglia

Abstract: Activation of p38 mitogen-activated protein kinase (p38) in spinal microglia is implicated in spinal nociceptive processing. Minocycline, a tetracycline derivative, displays selective inhibition of microglial activation, a function that is distinct from its antibiotic activity. In the present study we examined antinociceptive effects of intrathecal (IT) administration of minocycline in experimental models of inflammation-evoked hyperalgesia in addition to the effect of minocycline on stimulation-induced activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 49 publications
12
185
1
4
Order By: Relevance
“…Minocycline failed to modify the intracellular levels of Ca 2+ in resting conditions, and did not attenuate a Ca 2+ increase following cellular depolarization with 50 mM KCl. Our data also revealed that induced by intrathecal NMDA [46], or shed some light on the favourable effects of minocycline in a therapeutic window between 6 and 24 hours after a stroke [47].…”
Section: Discussionsupporting
confidence: 70%
“…Minocycline failed to modify the intracellular levels of Ca 2+ in resting conditions, and did not attenuate a Ca 2+ increase following cellular depolarization with 50 mM KCl. Our data also revealed that induced by intrathecal NMDA [46], or shed some light on the favourable effects of minocycline in a therapeutic window between 6 and 24 hours after a stroke [47].…”
Section: Discussionsupporting
confidence: 70%
“…Another groups using the same model also shows p38 activation in spinal microglia with slightly delayed time course (Tsuda et al, 2004). Other groups also demonstrate p38 activation in spinal microglia in different pain conditions (Hains & Waxman, 2006;Hua et al, 2005;Kim et al, 2002;Svensson et al, 2003;Svensson et al, 2005b;Xu et al, 2007a;Xu et al, 2007b). In the SNI model of neuropathic pain, the microglia activation of p38 is mostly seen in the medial part of the dorsal horn, where the injured tibial and peroneal nerves terminate .…”
Section: Map Kinase Activation In Microglia and Pain Controlmentioning
confidence: 85%
“…Upregulation of OX-42 or Iba1 is indicative of microglia activation. In inflammatory pain models that do not involve nerve injury, such as carrageenan model (Hua et al, 2005) and zymosan model (Clark et al, 2007a;Sweitzer et al, 1999), there is only a very moderate increase of OX42-immunoreactivity (IR) in the spinal cord. Whereas other models such as complete Freund's adjuvant model (Clark et al, 2007a;Zhang et al, 2003) and mustard oil model (Molander et al, 1997) fail to demonstrate any increase of OX-42-IR.…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathecal injection of ATP-activated microglia induces mechanical allodynia (a nociceptive response to normally innocuous mechanical stimulation) that requires microglial production of BDNF (Tsuda et al, 2003;Coull et al, 2005). A non-specific microglial inhibitor minocycline prevents/delays pain development (Raghavendra et al, 2003;Ledeboer et al, 2005;Hua et al, 2005). Notably, studies from different laboratories have demonstrated that p38 mitogen-activated protein kinase (MAPK) is activated in spinal microglia under different chronic pain conditions, and that blocking this kinase attenuates pain hypersensitivity (Table 1 ( Jin et al, 2003;Schafers et al, 2003;Tsuda et al, 2004;Boyle et al, 2006;Hains and Waxman, 2006).…”
Section: Introductionmentioning
confidence: 99%